2014
DOI: 10.1002/ptr.5205
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cerebral Nervous System Areas and Cytokines on Antihyperalgesic and Anti‐Inflammatory Activities of Kielmeyera rugosa Choisy (Calophyllaceae) in Rodents

Abstract: Kielmeyera rugosa is a medicinal plant known in Northeastern Brazil as 'pau-santo', and it is used in the treatment of several tropical diseases such as malaria, schistosomiasis, and leishmaniasis. We evaluated antihyperalgesic and anti-inflammatory activities of methanol stem extract of K. rugosa (MEKR) in mice. The mechanical hyperalgesia induced by carrageenan and tumor necrosis factor-alpha (TNF-α), prostaglandin E2 , and dopamine were assessed. We also investigated the anti-inflammatory effect of MEKR on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…They are known for the presence of ducts and resinous cavities that play an important role in defence of plants against herbivory, fungi and bacteria (Bittrich et al, 2015;Cabrita 2019). Also, these species are important from an economic point of view, as they have antiinflammatory, antioxidant, anti-tumour properties and are used in the treatment of skin diseases, such as pau-santo-rosa (K. rubriflora), pau-santo (K. coriacea), camac ßari (C. densifolia) and guanandi (C. brasiliense); these species are also planted for the recovery of disturbed areas and also offer good quality wood for civil construction (Souza & Lorenzi 2012;Melo et al, 2014;Morandi et al, 2017;Silva et al, 2020). The species conservation status has not yet been evaluated (CNC Flora 2021).…”
Section: Species Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are known for the presence of ducts and resinous cavities that play an important role in defence of plants against herbivory, fungi and bacteria (Bittrich et al, 2015;Cabrita 2019). Also, these species are important from an economic point of view, as they have antiinflammatory, antioxidant, anti-tumour properties and are used in the treatment of skin diseases, such as pau-santo-rosa (K. rubriflora), pau-santo (K. coriacea), camac ßari (C. densifolia) and guanandi (C. brasiliense); these species are also planted for the recovery of disturbed areas and also offer good quality wood for civil construction (Souza & Lorenzi 2012;Melo et al, 2014;Morandi et al, 2017;Silva et al, 2020). The species conservation status has not yet been evaluated (CNC Flora 2021).…”
Section: Species Selectionmentioning
confidence: 99%
“…Calophyllaceae (Malpighiales) is a Neotropical family in which different facets have been studied, including prospecting for chemicals and pharmaceuticals and ecological investigations (Caddah et al, 2012;Melo et al, 2014). The family comprises 14 genera and about 460 species and is characterized by shrubs, trees, or rarely, lianas, with a cream, white or translucent exudate (Stevens 2001 onwards).…”
Section: Introductionmentioning
confidence: 99%
“…Natural compounds have been used for different therapeutic applications, including antinociceptive (Almeida et al, 2015;Bonjardim et al, 2011;Franco et al, 2011;Melo et al, 2014), antioxidant (Paixão et al, 2013), and antiinflammatory (Veras et al, 2013;Paixão et al, 2015) activities. However, there are few studies that describe pharmacological effects of a nanostructured gel of thymol in acute periodontitis model.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study with methanol stem extract of Kielmeyera rugosa Choisy demonstrated antihyperalgesic and anti-inflammatory effects, and these effects were associated with the inhibition of cytokine cascade generated by carrageenan and/ or in decreasing the production of inflammatory mediators by significantly reducing the TNF-α and IL-1β (Melo et al 2014). This suggests that other species of the Kielmeyera genus display anti-inflammatory activity and also inhibit TNF-α.…”
Section: Resultsmentioning
confidence: 82%